Political Quota for Women and Gender-equitable Policies in Bangladesh. Issue 1 (June 2018) - Akbar, Tahsina
Ensuring women's participation in the parliament has been an important part of the women's movement around the world. Millennium Development Goal (MDG) number 3 further highlighted the significance of quota for women in the parliament to increase their average proportion. However, it has been a long-standing debate whether political quota for women helps promote more gender-equitable policies. This article intends to explore this critical question by discussing the quota system in Bangladesh and the translation of gender-equitable policies as an outcome. It uses the feminist institutionalism framework to analyse the national level political and social institutions. The article also discusses why increasing women's representation in the political arena alone (through quota system) does not automatically ensure gender-equitable policies; rather this transformation requires a combination of several policies.